ORGANIZATIONAL CULTURE AND RESILIENCE : SYSTEMATIC LITERATURE REVIEW - Muadzah, Syarifah; Suryanto, Suryanto (LPPM STIE Muhammadiah Bandung, 2024)
Organizations face numerous external challenges such as regulatory changes, market shifts, and emerging competition, necessitating quick adaptation and risk management for survival and optimal performance. Organizational culture, encompassing shared norms, beliefs, and systems, plays a crucial role in this adaptive capability, significantly influencing organizational resilience. Studies indicate that cultural factors such as flexibility, adaptability, and open communication enhance resilience, while leadership deficits and internal conflicts hinder it. Methodologically, this research uses a Systematic Literature Review (SLR) to synthesize findings from 20 studies, highlighting the centrality of organizational culture in fostering resilience. Different cultural dimensions, depending on the organizational context, impact resilience levels, with evidence suggesting that robust, adaptable cultures support better performance and mental health, and facilitate effective business processes. The study concludes that strategic human resource policies promoting a supportive and adaptive culture are vital for organizational success in dynamic environments. Recommendations for future research include deeper exploration of cultural impacts across sectors and the implementation of policies to enhance employee adaptability and leadership development, thereby reinforcing long-term organizational resilience.